2017
DOI: 10.1016/j.pmedr.2016.12.005
|View full text |Cite
|
Sign up to set email alerts
|

Pediatrician prescriptions for outdoor physical activity among children: A pilot study

Abstract: Research indicates that promoting time spent in the outdoors and outdoor physical activity increases children's daily physical activity and improves health. One method showing promise is doctor prescriptions for outdoor physical activity for children; however, no empirical evidence currently exists on prescriptions for children's outdoor physical activity. A pilot study was conducted at one pediatric practice in western North Carolina during 2015 to test the feasibility and potential effectiveness of conductin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
33
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(33 citation statements)
references
References 38 publications
0
33
0
Order By: Relevance
“…Few studies have been conducted on the impact of intervention programs that aim to encourage physical activity among youth as a preventive measure, strengthening their mental health and reducing risk factors that increase the probability of addiction or other problematic behavior on a personal and social level [ 9 , 10 , 11 , 26 ]. Findings from the present study reinforce the importance of cooperation between organizations devoted to promoting community health and between partnering organizations in the intervention program.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Few studies have been conducted on the impact of intervention programs that aim to encourage physical activity among youth as a preventive measure, strengthening their mental health and reducing risk factors that increase the probability of addiction or other problematic behavior on a personal and social level [ 9 , 10 , 11 , 26 ]. Findings from the present study reinforce the importance of cooperation between organizations devoted to promoting community health and between partnering organizations in the intervention program.…”
Section: Discussionmentioning
confidence: 99%
“…Physical activity can take place in a variety of environments, including parks that are usually accessible to the public. It is well known and has been established that parks provide good opportunities for promoting physical activity [ 7 , 9 , 10 , 11 , 36 ]. Findings of a recently published review on the association between parks and physical activity indicated a positive relationship between visiting parks and partaking in physical activity [ 36 , 37 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The articles with intersections begin with an intersection between a mother's dietary patterns during pregnancy period and childhood obesity [202], in addition to mother's depression and its relationship with infant health problems and abuse [2]. Other researchers covered different issues, such as vaccination strategies [203], traffic fatality [204], Oropharyngeal swab in children with cystic fibrosis (CF) [205], predictors of inflammation in infants [206], the association between serum levels of uric acid and blood pressure tracking in childhood [207], kindergarten barefoot policy's effect on preschool children's toes [208], added sugar consumption [209], socioeconomic status (SES) and child injuries [210] and prescriptions for outdoor physical activity among children [211]. The last few articles covered children's health effect on education [212], myotonic dystrophy [213], how household social capital and socioeconomic inequalities can result in child undernutrition [214] and how mother's empowerment relates to children's nutritional status [215].…”
Section: ) Other/healthmentioning
confidence: 99%
“…Although outdoor PA prescription programs are gaining momentum among HCPs, few studies have examined whether these programs effectively increase PA. 20 Of studies that have been conducted, investigations have focused on prescription program’s impact on children, 21 adults, 22 program distribution, 23 and program evaluation. 24 Few studies have investigated the challenges HCPs face incorporating prescription programs in their practice.…”
mentioning
confidence: 99%